Kadı Siraceddin El-Urmevî’nin Metafizik Anlayışı ve Metafizik Kavramlara Yaklaşımı - Öztürk Kocabiyik, Nilüfer (Dinî araştırmalar, 2022)
Metaphysics is one of the most major disciplines of philosophy. Generally, since Aristotle, its subject has been accepted as "being qua being". However, in the history of Islamic thought, there have been some scholars who think that kalam should be accepted as a superior science instead of metaphysics. Therefore, these thinkers considered "being qua being", which is accepted as the subject of metaphysics, as the subject of theology. In this study, the approach of Qadî Sirâj al-Din Urmawi, a member of the philosophical theology school formed by the philosophical-kalam scholars who think that the claim in question is true and is shaped within the framework of this idea to metaphysical science and metaphysical concepts will be discussed. Therefore, this study is limited to Urmawi’s approach to metaphysics and metaphysical concepts. With this study on Urmawi, it is aimed to determine the essential position of metaphysics according to Urmawi and the meanings of metaphysical concepts in his thought. It is important for the development of philosophical thought to determine the way in which these issues are handled by a thinker who is a member of the philosophical theological school. His works Matali al-Anwâr and Bayân al-Haqq, written in the line of Fakhr al-Din al-Razi, are remarkable in terms of revealing his philosophy and the way he dealt with metaphysical concepts in a broader way. Additionally, with this study, which will contribute to the understanding of the position of metaphysics in the 13th century, it is seen that metaphysics is a superior science in the eyes of Urmawi. However, his approach to metaphysical concepts is different from his approach to the science of metaphysics. Indeed, although he gives place to Ibn Sînâ’s views on metaphysical concepts, Fakhr al-Din al-Razi is dominant in his approaching.